2022
DOI: 10.3389/fpsyt.2022.1007144
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant frontolimbic circuit in female depressed adolescents with and without suicidal attempts: A resting-state functional magnetic resonance imaging study

Abstract: BackgroundThe neurobiological basis of suicidal behaviors among female adolescents with major depressive disorder (MDD) remains largely unclear.Materials and methodsFifty-eight drug-naïve, first-episode female adolescent MDD [including 31 patients with suicidal attempt (SA group) and 27 patients without SA (non-SA group)], and 36 matched healthy controls (HCs) participated in the present study. Resting-state functional magnetic resonance imaging (MRI) was performed on each subject. The metrics of the amplitude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 61 publications
2
3
0
Order By: Relevance
“…Our findings are partially in line with previous studies that reported abnormal ALFF values in the temporal and fusiform gyrus in depressed adolescents (7,24,25). For example, Cao et al found that young depressed patients with suicidal behavior had increased baseline brain activity in the left middle temporal gyrus (l-MTG) compared to those without suicidal behavior (7).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our findings are partially in line with previous studies that reported abnormal ALFF values in the temporal and fusiform gyrus in depressed adolescents (7,24,25). For example, Cao et al found that young depressed patients with suicidal behavior had increased baseline brain activity in the left middle temporal gyrus (l-MTG) compared to those without suicidal behavior (7).…”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, when combining the mean ALFF values of both regions, relatively successful discrimination was achieved, suggesting that a combination of different biomarkers may provide a better prediction of suicide attempts and infer a potential suicide risk in depressed adolescents. Our research findings are consistent with some of the results in the literature but also have some differences (7,25,45). Unlike Cao et al we did not find significant differences in the ALFF values in the l-SFG and l-MFG between the two groups, nor did this region have a good discriminative capability (7).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…As mentioned in Methods, we conducted an additional updated search in May 2023, after the data synthesis had been performed and the brain model of suicidal behavior in youth had been built. The search resulted in 8 papers that met the inclusion criteria [58][59][60][61][62][63][64][65]. To preserve the order of the data synthesis-in which we begin with the systematic literature search first, without any specific model in mind, then perform a narrative synthesis, and finally propose a model-we did not include the 8 additional papers in the synthesis and instead compared the findings in these papers to our END model as to whether they support or contradict it.…”
Section: Discussionmentioning
confidence: 99%
“…Recently a study has calculated a suicide prevalence of 8.76 per 100,000 inhabitants in Mexico and previous reports have estimated 804,000 annual suicides worldwide (Cabello-Rangel et al, 2020). Major Depressive Disorder (MDD) is one of the most common mental disorders, affecting over 320 million people worldwide, and has been associated with an increased risk of suicidal ideation (SI), suicide attempts (SA), and completed suicide (Liu et al, 2022;Xu et al, 2022).…”
Section: Introductionmentioning
confidence: 99%